2020
DOI: 10.29228/turkishstudies.41539
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinde Narsisizm ve Sosyal Onay İhtiyacı

Abstract: The aim of the this research is to investigate university students narcissism and social approval. The participants of this study, consisted of 248 undergraduate students (178 girls; 70 boys). This study, Five-Factor Narcissism Inventory-Short Form and The Need for Social Approval Scale were used to collect data. The Five Factor Narcissism Scale-Short Form was developed by Glover et al. (2012). The short-form of the 60-item scale was developed by Sherman et al. (2015). Ekşi (2016) adapted the Turkish version. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
2
2
0
4
Order By: Relevance
“…The need for social approval was also found to be not varying significantly depending on the birth order. Similar results have been found in different studies in the literature (Karaşar and Öğülmüş, 2016c;Karaşar and Öğülmüş, 2016d). It can be thought that the need for social approval may be higher in the first children because while bringing up their children parents may have invested more efforts for their first children to be respectful to others' opinions, to be more adaptive and to leave positive impressions; yet, in the current study, this was not confirmed and this might indicate that the need for social approval is a more universal need.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The need for social approval was also found to be not varying significantly depending on the birth order. Similar results have been found in different studies in the literature (Karaşar and Öğülmüş, 2016c;Karaşar and Öğülmüş, 2016d). It can be thought that the need for social approval may be higher in the first children because while bringing up their children parents may have invested more efforts for their first children to be respectful to others' opinions, to be more adaptive and to leave positive impressions; yet, in the current study, this was not confirmed and this might indicate that the need for social approval is a more universal need.…”
Section: Discussionsupporting
confidence: 91%
“…The need for social approval was also found to be not varying significantly in the pre-service teachers. Similar findings have been reported in many studies focused on this subject (Karaşar and Öğülmüş, 2016c;Karaşar and Öğülmüş, 2016d;Karaşar and Öğülmüş, 2017;Karaşar and Baytemir, 2018;Karaşar, 2020b). This might; as stated by Karaşar (2014), be because for cultural reasons, the need for social approval similarly affects both males and females.…”
Section: Discussionsupporting
confidence: 86%
“…Social approval is a concept that is related to attaching importance to others and their judgements and the individual's taking care of demonstrating behaviours towards adaptation in social interactions (Karaşar, 2014). Need for social approval-related new research studies were conducted with university students in Turkey (Karaşar 2014;Karaşar and Öğülmüş, 2016;Öğülmüş, 2016a, 2016b;2016c;Karaşar and Öğülmüş, 2017;Karaşar and Baytemir, 2018;Karaşar and Baytemir, 2018b;Karaşar, 2019;Karaşar, 2020;Raba, 2019;Turan, 2018). Social approval, very important for adolescents.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Sosyal onay ihtiyacı ile ilgili yapılan araştırmalara bakıldığında; Türkiye'de sosyal onay ihtiyacıyla ilgili araştırmaların yeni yapılmaya başlandığı ve sınırlı sayıdaki çalışmaların ise daha çok üniversite öğrencileri ile gerçekleştiği dikkat çekmektedir (Alagöz, 2019;Karaşar 2014;Karaşar, 2019;Karaşar, 2020;Karaşar ve Baytemir, 2018a;Karaşar ve Baytemir, 2018b;Karaşar ve Öğülmüş, 2016;Karaşar ve Öğülmüş, 2016aKaraşar ve Öğülmüş, , 2016bKaraşar ve Öğülmüş, , 2016cKaraşar ve Öğülmüş, 2017;Raba, 2019;Turan, 2018).…”
Section: Introductionunclassified
“…Sosyal onay ihtiyacı ile ilişkili alanyazın incelendiğinde, sosyal onay ihtiyacının akademik performans, problemli internet kullanımı, mutluluk, sosyal kaygı, mükemmeliyetçilik, benlik kurgusu, cinsiyet, doğum sırası, ebeveyne bağlanma, kişilerarası yeterlilik, akademik güdülenme, sosyal kaygı, sosyal medya kullanımı, çekirdek-geniş ailede yetişme, benliğin farklılaşması, ebeveyn sınav kaygısı, akılcı olmayan inançlar, iyilik hali, beden memnuniyeti, sosyal medya bağımlılığı, narsisizm, karşılıklı bağımlılık, depresyon, kendini sevme/öz yeterlik, öğrenme motivasyonu ve stratejileri, öğretmenlerin derecelendirme davranışı gibi çeşitli değişkenlerle ilişkilerinin araştırıldığı görülmektedir (Rothbart, Dalfen ve Barrett, 1971;Siyez, 2015;Karaşar ve Öğülmüş, 2016b;Baytemir, Karaşar ve Öğülmüş, 2017;Hewitt ve Flett, 1991;Davis, 1983;Masterson, 1971;Moran, 1967;Aydoğmuş ve Demir, 2017;Türkmen, 2019;Değirmenci ve Demirli, 2019;Baytemir, 2019;Yalçınkaya, Taner ve Demirci, 2019;Gökkaya, Deniz ve Gedik, 2020;Karaşar, 2020b;Karaşar, 2020a;Karaşar, 2021;Niles, 1995;Crowl, 2001;Ingman, 1999). Ancak araştırmanın yürütüldüğü zaman diliminde alanyazında sosyal onay ihtiyacının yordanmasında ilişkisel-bireyci-toplulukçu benlik ile ana-baba tutumunun rolünün birlikte incelendiği bir çalışmaya rastlanmamıştır.…”
Section: Introductionunclassified